Islands and Non-islands in Native and Heritage Korean - Kim, Boyoung; Goodall, Grant (Frontiers in Psychology, 2016)
To a large extent, island phenomena are cross-linguistically invariable, but English and Korean present some striking differences in this domain. English has wh-movement and Korean does not, and while both languages show sensitivity to wh-islands, only English has island effects for adjunct clauses. Given this complex set of differences, one might expect Korean/English bilinguals, and especially heritage Korean speakers (i.e. early bilinguals whose L2 became their dominant language during childhood) to be different from native speakers, since heritage speakers have had more limited exposure to Korean, may have had incomplete acquisition and/or attrition, and may show significant transfer effects from the L2. Here we examine islands in heritage speakers of Korean in the U.S. Through a series of four formal acceptability experiments comparing these heritage speakers with native speakers residing in Korea, we show that the two groups are remarkably similar. Both show clear evidence for wh-islands and an equally clear lack of adjunct island effects. Given the very different linguistic environment that the heritage speakers have had since early childhood, this result lends support to the idea that island phenomena are largely immune to environmental influences and stem from deeper properties of the processor and/or grammar. Similarly, it casts some doubt on recent proposals that islands are learned from the input.